2016
DOI: 10.3390/d8040032
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Rattus norvegicus in the South Atlantic Ocean

Abstract: Norway rats are a globally distributed invasive species, which have colonized many islands around the world, including in the South Atlantic Ocean. We investigated the phylogeography of Norway rats across the South Atlantic Ocean and bordering continental countries. We identified haplotypes from 517 bp of the hypervariable region I of the mitochondrial D-loop and constructed a Bayesian consensus tree and median-joining network incorporating all other publicly available haplotypes via an alignment of 364 bp. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
2
0
0
Order By: Relevance
“…In keeping with the earlier North Island introduction date, single base-pair mutations from the dominant haplogroup were only detected in the North Island. Similar within-archipelago independent introductions of R. norvegicus have also been found in the Falklands Islands (Hingston et al, 2016). Large gaps in our coverage of the South Island for R. norvegicus correspond with the extent of alpine and beech forest distribution in New Zealand (Wardle, 1984), from where R. norvegicus is seemingly absent.…”
Section: Discussionsupporting
confidence: 70%
“…In keeping with the earlier North Island introduction date, single base-pair mutations from the dominant haplogroup were only detected in the North Island. Similar within-archipelago independent introductions of R. norvegicus have also been found in the Falklands Islands (Hingston et al, 2016). Large gaps in our coverage of the South Island for R. norvegicus correspond with the extent of alpine and beech forest distribution in New Zealand (Wardle, 1984), from where R. norvegicus is seemingly absent.…”
Section: Discussionsupporting
confidence: 70%
“…Louys et al (2020) suggested that the Black rat arrived in Nusa Tenggara prior to the widespread dispersal of the Pacific rat from Flores, the Pacific rat's likely point of origin. The Pacific rat record followed the pattern found by others showing that, once dispersal began, a major haplotype group spread quickly through Nusa Tenggara and into the Pacific (Thomson et al, 2014;Matisoo-Smith et al, 2014;Hingston, 2015;West et al, 2017). In Flores, Black rats do not appear in the record of Liang Luar until about 400 years ago, while Pacific rats are recorded from at least 2500 BP (St Pierre, 2011).…”
Section: Discussionsupporting
confidence: 64%